The origin of 2.78 eV emission and yellow coloration in bulk AlN substrates - Sedhain, A.; Du, L.; Edgar, James H.; Lin, J. Y.; Jiang, H. X. (My University, 2009)
The yellow color of bulk AlN crystals was found to be caused by the optical absorption of light with wavelengths shorter than that of yellow. This yellow impurity limits UV transparency and hence restricts the applications of AlN substrates for deep UV optoelectronic devices. Here, the optical properties of AlN epilayers, polycrystalline AlN, and bulk AlN single crystals have been investigated using photoluminescence PL spectroscopy to address the origin of this yellow appearance. An emission band with a linewidth of ~0.3 eV (at 10 K) was observed at ~2.78 eV. We propose that the origin of the yellow color in bulk AlN is due to a band-to-impurity absorption involving the excitation of electrons from the valence band to the doubly negative charged state, (V[superscript]2-[subscript]Al), of isolated aluminum vacancies, (V[subscript]Al)superscript]3-/2- described by V[superscript]2-[subscript]Al)+hv=V[superscript]3-[subscript]Al)+h[superscript]+. In such a context, the reverse process is responsible for the 2.78 eV PL emission.
Keywords: Aluminium compounds; III-V semiconductors; Impurity absorption spectra; Photoluminescence; Semiconductor epitaxial layers; Vacancies (crystal); Valence bands; Wide band gap semiconductors